2022
DOI: 10.3389/fendo.2022.891233
|View full text |Cite
|
Sign up to set email alerts
|

Fish and the Thyroid: A Janus Bifrons Relationship Caused by Pollutants and the Omega-3 Polyunsaturated Fatty Acids

Abstract: Benefits of the omega-3 polyunsaturated fatty acids (PUFA) on a number of clinical disorders, including autoimmune diseases, are widely reported in the literature. One major dietary source of PUFA are fish, particularly the small oily fish, like anchovy, sardine, mackerel and others. Unfortunately, fish (particularly the large, top-predator fish like swordfish) are also a source of pollutants, including the heavy metals. One relevant heavy metal is mercury, a known environmental trigger of autoimmunity that is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 206 publications
0
11
0
Order By: Relevance
“…Therefore, future studies should specifically analyze the impact of dietary diversity on health according to individual health cognition and economic status, and pay attention to food attributes and diet balance. Some studies have also found an increase in thyroid disease in people exposed to polluted environmental and food, such as petrochemical workers, areas contaminated with organochlorine pesticides or polychlorinated biphenyls, or near aluminum foundries ( 45 , 53 ). Fish (particularly the large, top-predator fish like swordfish) from polluted waters have more likely high levels of mercury.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, future studies should specifically analyze the impact of dietary diversity on health according to individual health cognition and economic status, and pay attention to food attributes and diet balance. Some studies have also found an increase in thyroid disease in people exposed to polluted environmental and food, such as petrochemical workers, areas contaminated with organochlorine pesticides or polychlorinated biphenyls, or near aluminum foundries ( 45 , 53 ). Fish (particularly the large, top-predator fish like swordfish) from polluted waters have more likely high levels of mercury.…”
Section: Discussionmentioning
confidence: 99%
“…Mercury was found to be a known autoimmune environmental trigger and can be measured inside the thyroid ( 54 ). Fortunately, nutrients such as omega-3 fatty acids and selenium found in fish have been shown to exert a protective effect against thyroid disease and reduced the risk of cancer ( 53 ). Therefore, future research should not ignore the possibility of food contamination.…”
Section: Discussionmentioning
confidence: 99%
“…Although the mechanism of the association between hypothyroidism and cognitive dysfunction is not precise, it is still essential to focus on the prevention of hypothyroidism. Modifying iodine deficiency [64] or iodine excess [65], nutraceuticals such as omega-3 PUFA supplementation [66], and improving sleep quality [67] all have positive implications. Accurate assessment of whether hypothyroidism is associated with an increased risk of dementia or cognitive impairment is important for the accurate prevention and treatment of dementia.…”
Section: Discussionmentioning
confidence: 99%
“…We read with interest the paper published in the journal by Benvenga S, et al (1) about the complex interplay between thyroid disorders and the intake of omega-3 polyunsaturated fatty acids (PUFAs), whose main dietary source is represented by fish. In their review, Benvenga et al (1) put a specific warning on the potential heavy metal content in fish and the risks deriving from its consumption, suggesting that there would be the place for the use of nutraceuticals containing omega-3 PUFAs to prevent or contrast autoimmune thyroiditis, overcoming the risk of contaminants in fish. Although pharmacological supplementation would be sometimes useful, also limiting dietary consumption to fishes containing low levels of pollutants and including fish within the framework of a healthy diet represent a good choice.…”
Section: Introductionmentioning
confidence: 99%
“…We read with interest the paper published in the journal by Benvenga S, et al. ( 1 ) about the complex interplay between thyroid disorders and the intake of omega-3 polyunsaturated fatty acids (PUFAs), whose main dietary source is represented by fish. In their review, Benvenga et al.…”
Section: Introductionmentioning
confidence: 99%